(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
’Health promotion is the process of enabling individuals to increase control over and to improve their health’. This surge of public health is rising as a critical domain inside the domain of infection counteractive action. Throughout the most recent two decades, the remedial model of health care has started an unobtrusive move towards a participatory model of health promotion endless supply of healthy ways of life and making healthy networks. Health promotion encompasses five key systems with health communication and education as its foundations. Present investigation is an attempt to investigate the present circumstance of health promotion education in India with a mean to give a foundation to limit working in health promotion. The quality of human health is the foundation whereupon the realization of life objectives and destinations of a persona, the network or country as entire depends. It is both an end and methods for development system. The connection among health and development is mutually fortifying while health adds to economic development, economic development, thus, will in general improve the health status of the populace in a nation. India as a country has been growing economically at a rapid pace especially after the approach of New Economic Policy of 1991. Be that as it may, this rapid economic development has not been joined by social development especially health sector development.